Ready for the Robot: Bovines in the Integrated Circuit - Calvert, Scout (Humanimalia, 2018)
Situating cows as co-laborers in global technology sectors, “Ready for the Robot” explores the predicament of cows working as robot operators, information workers, and data producers. The data cows produce shape the conditions in which they work, including their own bodies, as statistical evaluations of cattle abstract profitable traits and warp their connection to breed. Milking robots are posited as providing freedom to dairy cows, but this is far from guaranteed. Rather, cow bodies are programmed to fit the limitations of the robot and the routines of the automated farm, coding that breaches categories of breed. Drawing on Donna Haraway’s Cyborg Manifesto, this article argues for a “cowborg politics” that shapes technology for new research questions and methods that produce genuinely better working conditions for cows and their human companions and co-workers.